Effect of gold nanoparticles laced anode on the bio-electro-catalytic activity and power generation ability of compost based microbial fuel cell as a coin cell sized device. (September 2021) - Magotra, Verjesh Kumar; Kang, T.W.; Aqueel Ahmed, Abu Talha; Inamdar, Akbar I.; Im, Hyunsik; Ghodake, Gajanan; Choubey, Ravi Kant; Kumar, Vijay; Kumar, Sunil
Abstract: As anodic performance can control the bio-electro-catalytic activity and overall power generation ability of cheaper compost based microbial fuel cells (MFC), bio-compatible gold nanoparticles (AuNPs) laced carbon fiber electrode is used for enhancing the efficiency. Casein peptide as a reducing and capping agent is used to synthesize bio-functional cubic AuNPs with absorption wavelength of 530 nm. The results of Cyclic Voltammetry (C–V) and electrochemical impedance spectroscopy shows that AuNPs laced electrode exhibited increased current density and better bio-electro-catalytic activity than the bare electrode which shows selective response with respect to type of compost and fuel concentration in a coin cell sized MFC. Current-Voltage (I–V) measurements show that due to the increase in the bio-electro-catalytic activity, the electrical power increases from 1.6 mW per m 2 to 18.34 mW per m 2 at room temperature in case of carbon rich compost at an optimized fuel concentration of 0.2 g per ml. The temperature dependence bipolar C–V measurements shows the enhancement in bio-electro-catalytic activity with increase in temperature. Also, significant improvement in durability and stability of MFC was observed with the lacing of AuNPs. Graphical abstract: Image 1 Highlights: Gold nanoparticles laced anode increases the bio-electro-catalytic activity. Enhancement of bio-electro-catalytic activity leads to efficient generation of energy. Coin cell sized microbial fuel cell is optimized. Microbial action is the dominant behavior as proved by autoclave studies. This work also elucidates the development of injection type microbial fuel cell.